Hybrid Work: Is it a Blessing or a Curse? - Andreeva, Tatiana (2022)
Enabled by new technologies and informed by the experiences during COVID pandemic, many employees would like to continue working remotely (Teevan et al., 2022), as this enhances their work-life balance and well-being (George et al., 2021). Many leaders, on the contrary, would like to see their employees back to the office (Microsoft, 2022). To address this challenge, many organisations are considering moving to the hybrid work arrangements, allowing their employees to work some days in the remote settings, but requesting them to be in the office some other days (e.g., Barerro et al., 2022). This approach is often seen as a solution that meets the interests of both employees and employers and can capture the benefits of both remote and in-office work (e.g., Choudhury et al., 2022). But does hybrid work really work?